1993
DOI: 10.1097/00132586-199312000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Emla Cream, Subcutaneous Ring Anaesthesia and a Double Cuff Technique in the Prevention of Tourniquet Pain

Abstract: We have examined the effect of EMLA on tourniquet pain and compared it with those of subcutaneous ring anaesthesia (SRA), a double cuff technique and a single cuff (control) during i.v. regional anaesthesia. The durations of analgesia (mean 57.3 (SD 16.6) min) and tolerance (72.3 (13.9) min) to tourniquet inflation in the EMLA group were comparable to those in the SRA group (54.1(16.2) min and 68.3(19.0) min), but significantly (P < 0.05) greater than those in the control group (30.0 (10.7) min and 45.6 (14.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The expansion of the receptive fields of primary proximal nociceptors inherent to the tourniquet may explain the relative resistance of this pain to an otherwise adequate level of anaesthesia. Skin could contribute significantly to the superficial component of tourniquet pain [16, 17]. Muscle pain could also play a part in tourniquet pain during inflation and after tourniquet release [18], metabolic changes have, however, shown significant correlation with tourniquet time, but not with tourniquet pressure [19].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of the receptive fields of primary proximal nociceptors inherent to the tourniquet may explain the relative resistance of this pain to an otherwise adequate level of anaesthesia. Skin could contribute significantly to the superficial component of tourniquet pain [16, 17]. Muscle pain could also play a part in tourniquet pain during inflation and after tourniquet release [18], metabolic changes have, however, shown significant correlation with tourniquet time, but not with tourniquet pressure [19].…”
Section: Discussionmentioning
confidence: 99%
“…Tsai YC et al, compared EMLA cream, subcutaneous ring anesthesia and double cuff technique in the prevention of tourniquet pain and concluded double cuff technique to be most effective. 26 The peripheral perineural injection of morphine for chronic intractable pain was found to produce local analgesia without the use local anaesthetic and its duration of action was found to be longer than that of systemic morphine and that of bupivacine. 27 Contrary to the traditional view that opioid antinociception takes place exclusively within central nervous system, there are peripheral opioid receptors that mediate analgesia, when activated by exogenous opioid agonists applied in the vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have shown that subcutaneous ring anaesthesia and EMLA both significantly reduce or prevent tourniquet pain in intravenous anaesthesia of the arm [6, 7]. Brachial plexus block achieved by the axillary approach does not sufficiently anaesthetise the inner portion of the upper arm, an area where usually the tourniquet is applied.…”
Section: Discussionmentioning
confidence: 99%